pH-Triggered Magnetic-Chitosan Nanogels (MCNs) For Doxorubicin Delivery: Physically vs. Chemically Cross Linking Approach - Sadighian, Somayeh (Adv Pharm Bull, 2015)
Purpose: This paper evaluates the impact of cross linking strategy on the characteristics of magnetic chitosan nanogels (MCNs) as targeted drug delivery system for doxorubicin. Methods: Sodium tripolyphosphate (TPP) and glutaraldehyde were used as physical (electrostatic) and chemical (covalent binding) cross-linker agents, respectively. MCNs were characterized by means of X-ray diffraction (XRD), Scanning electron microscopy (SEM), fourier transform infrared (FT-IR) spectroscopy and vibrating sample magnetometer (VSM). Scanning electron microscopy (SEM) indicated the formation of spherical nanostructures with the final average particle size of around 35-40 nm. Results: The finding proved the superparamagnetic properties of the MCNs with relatively high-magnetization values which indicate that the MCNs were enough sensitive to external magnetic fields as a magnetic drug carrier. To understand the differences between the drug delivery properties of chemically and physically cross linked MCNs, the drug release studies were also conducted. Altogether, the results of this study clearly indicate that, however, both MCNs exhibited sustained drug release behaviour, the chemically cross linked MCNs provided enhanced controlled drug release characteristics in comparison to physically cross linked MCNs. Besides, according to the drug release behaviour of MCNs in buffer solutions in two different medium with the pH values of 5.3 and 7.4, it was clear that both nanoparticles exhibited pH sensitivity where the extent of drug release in the acidic media was significantly higher than neutral media. Conclusion: It can be concluded that chemically cross linked MCNs may serve as an ideal carrier for stimuli-triggered and controlled anticancer drug delivery.